The Impact of Cigarette Smoking on Oxidative Stress Indices - , Saheed Ladipo Kakako; , Ibrahim Shuaibu; , Ibrahim Abdullahi Musa; , Muhammad Lawal Jidda; , Sarafadeen Adeniyi Arisegi; , James Oyeniyi; , Idris Olawale Tajudeen; , Zainab Najim; , Kafilat Taiwo Salvador-Oke; , Taofeeq Bolarinwa Lawal; , Kabiru Bello Aliyu (Archives of Current Research International, 2025)
Introduction: Despite the shocking caption ‘Smokers are liable to die young’, the prevalence of cigarette smokers continues to surge, especially among the youth. Cigarette smoking is a notable health concern globally and is a well-known risk factor for many diseases including cancer and cardiovascular diseases. Cellular damage due to oxidative stress occurs when there is an imbalance between the body's antioxidant defense mechanism and pro-oxidants (chemicals in cigarettes). This study aimed to assess oxidative stress indices in cigarette smokers. Methods: A total of 100 cigarette smokers were recruited from various locations in the Sokoto metropolis and 50 apparently healthy nonsmokers as control. Demographic and clinical information were obtained using a standard questionnaire. Using a standard procedure, about 5 ml of blood sample was collected from each participant to analyze serum total antioxidant capacity (TAC) and total plasma peroxide (TPP) using the ferric-reducing ability of plasma and ferric xylenol orange-2 method, respectively. Results: A total of 54% of the participants were between 20-29 years of age and 63% were school certificate holders while the most frequently smoked cigarette is Bensen. The oxidative stress indices percentage (OSI %) was calculated. The result shows a significant positive correlation between TAC and TPP, and negatively correlated with OSI% (p<0.05, r= 0.261 and p<0.05, r= -0.332). Also, TPP shows a significant positive correlation with OSI% (p<0.05, r= 0.316). Conclusion: This study indicates that cigarette smoking is well associated with increased free radicals leading to the generation of oxidative stress. This accentuates the harm that has been established with cigarette smoking. We hope this will alert and dissuade nonsmokers from picking up smoking and encourage smoke cessation among chain smokers.